"I Am Double The Bi": Positive Aspects of Being Both Bisexual and Biracial. Issue 2 (3rd April 2019) - Paz Galupo, M.; Taylor, Son M.; Cole, David
Abstract: The present research investigates the positive experiences of individuals who identify as bisexual/plurisexual and biracial/multiracial. Participants included 107 adults who self-identified as bisexual. Participants individually completed an online survey in which they were asked a series of questions regarding their identities. The majority of our participants (73.8%) reported positive experiences related to having dual bi identities. Qualitative responses were analyzed via thematic analysis and four major themes were identified: (1) uniqueness of being, (2) multiplicity of experience, (3) community connections, and (4) strengths and impact. Discussion focuses on understanding these positive experiences as being framed against a backdrop of minority stress, and in the context of intersectionality.